RE-LAYOUT SHOPFLOOR DEPARTMENT AT RETAIL COMPANY TO OPTIMIZE THE INITIAL LAYOUT, MATERIAL HANDLING REDUCTION, AND TRANSPORTATION WASTE MINIMIZATION USING BLOCPLAN ALGORITHM - Wardhana, Kresna Adji Setya; Cahyo, Winda Nur (Journal of Industrial Engineering and Technology, 2024)
Starcorss shopfloor employee (receiving and warehousing department) at headquarter stated on very high level of mental workload while high season compared while low season. Based on this consideration, the business owner asked the author personally to develop a new layout for shopfloor department as mitigation for mental workload based on previous research recommendation. Most likely 3 month the author has direct observed and proposed am optimized shopfloor layout with BLOCPLAN Algorithm approach. The proposal also considers about how to reduce waste activities on the shopfloor regarding material handling.